NAPZA, HIV & AIDS Dalam Perspektif Remaja: Rekomendasi Kebijakan Untuk Pengendalian Perilaku Beresiko - Dwi Nur Siti Marchamah; Wahyuni Arumsari; Risas Dika Maulana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2025)
Background: Adolescents are a group vulnerable to risky behaviors such as promiscuity, drug abuse, and HIV & AIDS infection, due to limited understanding and access to accurate information. Objective: This study aims to evaluate the level of adolescents' understanding of drugs, HIV & AIDS, and identify existing misconceptions as a basis for developing appropriate prevention education strategies. Method: This study used a mixed-methods approach with a sequential explanatory design. It was conducted in July-September 2025 at SMP Negeri X Semarang. The study population included all 355 adolescents at the school, with a sample of 188 adolescents determined using the Slovin Formula and cluster random sampling techniques. Quantitative data were collected through questionnaires, while qualitative data were obtained from interviews with 5 adolescents. Results: The analysis shows that the majority of adolescents have a good understanding of drugs, HIV & AIDS. However, there are misconceptions about how HIV is transmitted. This finding emphasizes the need for more in-depth educational interventions to correct these misunderstandings. Conclusion: Further education is needed so that adolescents are more selective in receiving information related to drugs, HIV & AIDS, and reduce risky behaviors. Schools are expected to strengthen supervision and provide more comprehensive education, including through mass media and social media platforms, to make prevention programs more effective.